2008
DOI: 10.1614/ws-07-118.1
|View full text |Cite
|
Sign up to set email alerts
|

Weed Interference, Pulse Species, and Plant Density Effects on Rotational Benefits

Abstract: Pulse crop management can increase pulse yields and N fixation, but the effects of previous pulse crop management on subsequent crop performance is poorly understood. Field studies were conducted at three locations, in the Parkland region of Alberta, Canada, between 2004 and 2006. Tannin-free faba bean, narrowleaf lupin, and field pea were planted at 0.5, 1.0, 1.5, and 2.0 times the recommended pulse planting density (PPD), with or without barley as a model weed. Faba bean produced the highest seed yields in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 52 publications
3
40
0
Order By: Relevance
“…Cultivated faba bean is mainly used as human food in developing countries and as animal feed for pigs, horses, poultry, and pigeons in industrialized countries (Rubiales, 2010;Flores et al, 2012). Faba bean is a very promising crop thanks to its protein value, high stem strength compared to other legumes and its adaptation to a range of temperate growing conditions (Strydhorst et al, 2008;Jensen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Cultivated faba bean is mainly used as human food in developing countries and as animal feed for pigs, horses, poultry, and pigeons in industrialized countries (Rubiales, 2010;Flores et al, 2012). Faba bean is a very promising crop thanks to its protein value, high stem strength compared to other legumes and its adaptation to a range of temperate growing conditions (Strydhorst et al, 2008;Jensen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Plant density is a key component in an integrated weed management program. In many situations, high plant density is demonstrated to provide substantial weed control (Beckie et al 2008;Strydhorst et al 2008). In an organic oat (Avena sativa) cropping system, for example, the combination of competitive genotype, increased plant density, and post-emergence harrowing decreased weed biomass by 71% compared with standard practices (Benaragama and Shirtliffe 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, their poor suppressive ability could be due to their susceptibility to allelopatic compounds released from roots and leaves of weed that resulted in retardation of the activities of nitrogen fixing bacteria which in line with [22], noted that a wide range of plant species affected by allelopathic inhibition of parthenium. Similarly, [23] reported that Faba bean (Vicia faba L.) had a higher nitrogen fixating ability in absence than presence of weed.…”
Section: Effect Of Test Species On Other Growth Attributes Of Partheniummentioning
confidence: 93%